“ENDA KALAK SINGKEL” STRENGTHENING CONSCIOUSNESS OF COMMUNITY IDENTITY OF ACEH’S BORDER; ETHNIC CONTESTATION AND RELIGION IN SINGKIL - Muhajir Al-Fairusy; Irwan Abdullah (Islam Futura, 2020)
This study is an effort to look deeper into the movement to strengthen ethnic identity in Singkil, Aceh. Singkil is one of the border districts of Aceh, and is actually affiliated with the meaning of an area that is inhabited by cross-ethnic and religious communities. So far, the Singkil community has identified itself on a territorial basis; pesisir and hulu. The Singkil Pesisir community is characterized by the use of the Malay-Minang language and settling along the coast. As for the hulu community, they are often identified as part of Pakpak and Alas because they use the kampung language (similar to the Pakpak language), most of whom live on the edge of the Singkil river. Even so, in the last half decade, discourse emerged through a cultural movement initiated by a handful of elite hulu communities, by campaigning for the Singkel (original) term, accompanied by the rejection of Pakpak label as the identity of Singkel as self identity. The question arises as to why ethnic identity strengthens in the midst of the Singkil community's communal life, which should be integrated in one regional identity. The purpose of this study is to measure descriptively the strengthening of ethnic identity in Singkil Regency. The research method used is qualitative with a grounded research approach. Data was also collected through reading related to the study of identity and the Singkil community. The results of the study indicate, if the awareness of ethnic identity strengthens amid the diversity of the Singkil community due to several factors; socio-political, religious, economic conditions and denial of identification of outsiders to the Singkil hulu identity are Pakpak sub-ethnic groups which are seen as degrading.